Hybrids Diazine: Recent Advancements in Modern Antimicrobial Therapy - Mangalagiu, Violeta; Danac, Ramona; Diaconu, Dumitrela; Zbancioc, Gheorghita; Mangalagiu, Ionel I. (Current Medicinal Chemistry, 2024)
Nowadays, antimicrobial therapies have become a very challenging issue because of a large diversity of reasons such as antimicrobial resistance, over consumption and misuse of antimicrobial agents, etc. A modern, actual and very useful approach in antimicrobial therapy is represented by the use of hybrid drugs, especially combined five and six-membered ring azaheterocycles. In this review, we present an overview of the recent advanced data from the last five years in the field of hybrid diazine compounds with antimicrobial activity. In this respect, we highlight here essential data concerning the synthesis and antimicrobial activity of the main classes of diazine hybrids: pyridazine, pyrimidine, pyrazine, and their fused derivatives.
Keywords: pyrazine